Lung abscess in congenital cystic malformation during early infancy - Subba, Gangaraj; Bhojraj, Shashank (International Journal of Contemporary Pediatrics, 2016)
Congenital Pulmonary Airway Malformation (CPAM) previously known as Congenital cystic adenomatoid malformations (CCAM) also known as congenital pulmonary airway disease is a developmental, non-hereditary hamartomatous abnormality of lung of unknown cause. Lung abscess is a rare condition and much rarer in early infancy. If CPAM is suspected as the cause of repeated pulmonary infection limited to single lobe, patient should be treated early with surgical removal of the affected lobe as Type I CPAM the most frequent subtype, is associated with risk of malignant transformation. We present a 52days old child presented with lung abscess in CPAM.